Measurement of Logistic Performance of Imported Frozen Meat in Perum Bulog - Rizki Nanditasari; Sukardi; M. Syamsul Maarif (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Perum BULOG received a mission to import frozen meat by the government in accordance with Presidential Regulation of the Republic of Indonesia Number 48 of 2016. As a company engaged in food logistics, Perum BULOG is expected to be able to carry out imported frozen meat logistics activities to meet domestic needs. Logistics activities of imported frozen meat in Perum BULOG are divided into three stages, starting from the assignment mechanism, import mechanism, and sales mechanism. This causes the realization of frozen meat has not been achieved in accordance with the assignment. This study aims to measure the logistics performance of the imported frozen meat logistics activities carried out by the State Logistics Agency. The analytical method used the Logistic Scorecard Model, by identifying business strategies to obtain KPIs, and compiling logistical performance measurements. The results obtained by the logistics performance score of 2.691. This means that logistical performance for imported frozen meats run by Perum BULOG is at level 2, so Perum BULOG's logistics performance is poor. The improvement recommendation is by making a map of the frozen meat commodity business and making a direct shipping distribution strategy. Keywords: activities of logistics, logistics performance measurement, logistic scorecard, perum bulog, frozen meat